Prinsip Keadilan Dalam Poligami: (Studi kasus KH. Ahmad Masruh IM, M.H Dan KH. Muhammad Farid Zaini Lc.) - Yayat Dimyati; Ferlina Revian Astuti (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2023)
Abstract: The factors studied in this study relate to the principle of fairness in polygamy: multisite kh studies. Ahmad Masruh IM and KH. Muhammad Farid Zaini. The purpose of this research is to know the practice of polygamy as well as the principle of justice according to kh thinking. Ahmad Masruh IM and KH. Muhammad Farid Zaini on justice in polygamy.This research uses qualitative method with qualitative field research method and this research uses descriptive qualitative approach related to events and events that occur at this time. The result of this study is about the principle of justice in the practice of polygamy where the principle of justice is only given to the husband, if the husband is able to provide for a living, a place to live, and a turnaround time, then the husband is said to be able to do justice.Polygamy is an inevitability that exists in Islam. The basic principle of polygamy is an element of justice. One factor shows fairness in clothing, food, boards and mu'amalah between his wife. As for justice that is love and compassion will not be able to be fair. So that a husband keeps himself, do not overdo it with one of his wives. It can be seen in the historical fact that the prophet, companions, tabi'in and many Muslims who do polygamy is a man who has goodness above good, this is special personally and in general for the wider community. As for those who argue that polygamy is forbidden because it considers the impossibility of justice in polygamy. Justice in polygamy in Islam is limited in three ways, the first is the amount, the second is the living and the third is justice between wives. In principle, the two verses above state that the principle of marriage is polygamy and an exception to monogamy. But by the rule that al-ahlu da'iman yuqoddamu al-istitsna'. It means adalag istisna' always preceded by principle, because knowledge is strengthening.